Self-tuning control for rotational inverted pendulum by eigenvalue approach - Ratiroch-Anant, Phornsuk; Anabuki, Masatoshi; Hirata, Hiroshi (My University, 2004)
The self-tuning strategy concerning the stabilized control system of the rotational inverted pendulum is considered. In the case of the pendulum with expansion and contraction under the stabilization, the system parameter is recursively estimated and the redesigned controller is appropriately updated. The available disturbance torque is appended to the control signal because the inverted pendulum does not have sufficient information for the estimation of the system parameter under the stabilization. It is verified by the practical experiment that the proposed self-tuning is very usefiil as one of the on-line tuning. © 2004IEEE.